Rapid accurate point-of-care tests combining diagnostics and antimicrobial resistance prediction for Neisseria gonorrhoeae and Mycoplasma genitalium. (6th July 2017) - Sadiq, Syed Tariq; Mazzaferri, Fulvia; Unemo, Magnus
Abstract : In addition to inadequate access to early diagnosis and treatment with antimicrobial agents for patients and sexual contacts, management and control of STIs is significantly challenged by emergence and spread of antimicrobial resistance (AMR), particularly for STIs such as Neisseria gonorrhoeae and Mycoplasma genitalium . This is further compounded by use of nucleic acid amplification techniques for diagnosis, resulting in reduced phenotypic AMR testing for N. gonorrhoeae and absence or suboptimal AMR surveillance for guiding treatment of both STIs in many settings. Rapid accurate point-of-care (POC) tests for diagnosis of all STIs would be valuable but to significantly impact treatment precision and management of N. gonorrhoeae and M. genitalium infections, combinations of rapid POC diagnostic and AMR testing (POC-AMR) will likely be required. This strategy would combat STI burden and AMR emergence and spread by enabling diagnosis and individualised treatment at the first healthcare visit, potentially reducing selection pressure on recommended antimicrobials, reducing transmission of resistant strains and providing means for AMR surveillance. Microfluidic and nanotechnology platforms under development for rapid detection of STIs provide a basis to also develop molecular rapid POC-AMR prediction. A number of prototypic devices are in the pipeline but none as yet approved for routine use. However, particularly for N. gonorrhoeae, more knowledge is required to assess which antimicrobials lend themselves to a genotypic POC-AMR approach, in relation to genotypic–phenotypic associations and potential impact clinically and epidemiologically. Key for successful deployment will include also understanding cost-effectiveness, cost-consequences and acceptability for key stakeholders.